Long-term outcomes and quality of life in patients with Hirschsprung disease - Mikko P Pakarinen; Annika Mutanen (BMJ Publishing Group, 2024)
Although patients with Hirschsprung disease are mostly affected by imperfect bowel function and fecal control in the long term, they are also predisposed to lower urinary tract symptoms, impaired sexual functions, infertility, psychosocial issues, and decreased quality of life. Rare, but notable comorbidities, which may manifest after childhood, include inflammatory bowel disease and familial medullary thyroid cancer. Despite frequent occurrence of fecal incontinence and constipation, the overall long-term outlook is quite optimistic as social continence with a good quality of life can be achieved by efficient bowel management also in those affected patients, whose self-coping strategies and medical treatment remain insufficient. Bowel dysfunction and other potential long-term complications are best managed by an interdisciplinary specialized approach not overlooking psychosocial issues, which also helps to correctly identify areas requiring continuing input by adult healthcare for young adult patients after transition. Additional research is needed to unravel the pathophysiological mechanisms of the long-term bowel dysfunction to identify novel therapeutic targets for development of more efficient innovative management strategies and thereby improvement of quality of life.